Effect of Firm Size and Corporate Governance Practice Earning Management - Chairul Anwar; Damabrata Anugrah (Universitas Bandar Lampung (UBL), 2015)
The purpose of this study demonstrate empirically the effect of firm size proxied by total assets andtotal sales as well as corporate governance mechanisms are proxied by the proportion of independent directors, the size of the board of directors and audit committee size of the earnings management practices in companies listed on the Indonesia Stock Exchange. This population is the entire manufacturing companies listed in Indonesia Stock Exchange from 2009 to 2013 years. Companies that were sampled 24 companies and the number of observations made during the years2009 to 2013 are 120 items observation. Methods of data analysis in this study using multiple linear regression. Based on the test results obtained by the value of R2 value of 0.516, which means, 51.6% of earnings management variables can be explained by the variable size of the company, the proportion of independent directors, the size of the board of directors, and the size of the audit committee. While the remaining 48.4% is explained by other factors that are not tested in the research. Based on the results of statistical tests showed that only the variable size of the board of directors who have no effect on earnings management, whereas the variable total assets, number of sales, the proportion of independent directors and audit committee size negatively affect earnings management.